Transportation of Children in Ground Ambulances: Professionals' Knowledge and Safety Measures - Lomba, Maria de Lurdes Lopes de Freitas (2016)
Background: The transport of children in ground ambulances is a rarely studied topic worldwide. The ambulance vehicle is a unique and complex environment with particular challenges for the safe, correct and effective transportation of patients. Unlike the well developed and readily available guidelines on the safe transportation of a child in motor vehicles, there is a lack on consistent specifications for transporting children in ambulances. Nurses are called daily to transfer children to hospitals or other care centers, so safe transport practices should be a major concern. Purpose: to know which are the safety precautions and specific measures used in the transport of children in ground ambulances by nurses and firefighters and to identify what knowledge these professionals had about safe modes of children transportation in ground ambulances. Methods: In this context, an exploratory - descriptive study and quantitative analysis was conducted. A questionnaire was completed by 135 nurses and firefighters / ambulance crew based on 4 possible children transport scenarios proposed by the NHTSA (National Highway Traffic Safety Administration) and covered 5 different children´s age groups (new born children, 1 to 12 months; 1 to 3 years old; 4 to 7 years old and 8 to 12 years old). Results: The main results showed a variety of safety measures used by the professionals and a significant difference between their actual mode of transportation and the mode they consider to be the ideal considering security goals. In addition, findings showed that achieved scores related to what ambulance crews do in the considered scenarios reflect mostly satisfactory levels of transportation rather than optimum levels of safety, according to NHTSA recommendations. Variables as gender, educational qualifications, occupational group and local where professionals work seem to influence the transport options. Female professionals and nurses from pediatric units appear to do a safer transportation of children in ground ambulances than other professionals. Conclusion: Several professionals refereed unawareness of the safest transportation options for children in ambulances and did not to know the existence of specific recommendations for this type of transportation. The dispersion of the results suggests the need for investment in professional training and further regulation for this type of transportation.